Commodification of culture in fiction-induced tourism - Lipovšek Emilija; Kesić Smiljka (University Educons, Faculty of Sports and Tourism, Novi Sad, 2015)
In the fiction-induced tourism, the illusion of the fictional world is maintained for the sake of the tourist in the real locations and thus it can be used to attract readership and cinephiles alike. Their desire to travel is based on the chronotope (Bakhtin, 1981) that is used as the background in their favourite books and films. Upon reading a book or seeing a film, the audience is inspired to visit the locations in a city where the plot took place. Thus the chronotope of the city featured in fiction develops palimpsestic features. If the flâneur experiences the city, its streets and inhabitants as he/she wanders aimlessly and translates afterwards all this into words in the urban narrative (Benjamin, 1968), then the tourist acts as a 'flâneur ranversé', while they walk the city and observe it in search of the places described in their favourite works of fiction. Moreover, the paper will consider some of the examples of the commodification of cultural products, including Harry Potter bookshop, guided walks and themed studio tours.